Scalable Ambient Synthesis of Metal-Organic Frameworks and Their Derivative Nanoporous Carbon for Superior Potassium Ion Storage - Lee, Giwook; Kim, Kangseok; Lim, Eunho; Hwang, Jongkook (ACS Sustainable Chemistry and Engineering, 2024)
Large-scale production of metal-organic frameworks (MOFs) under standard atmospheric conditions is of significant interest due to their cost-effectiveness and energy efficiency. However, such approaches often require excessive organic ligands or harmful additives to overcome the substantial energy barrier for nucleation. In this study, we present a scalable synthesis of zinc MOFs ([Zn2(BDC)2DABCO]n (ZnBD)) with a high space-time yield exceeding 2400 kg m-3 day-1 under ambient conditions, employing only stoichiometric amounts of reactants and no additional additives. Zinc acetate forms soluble dimers that mimic the structure of the secondary building units (SBUs) of ZnBD. This structural similarity facilitates ligand exchange between acetate and organic ligands, thereby lowering the energy barrier for nucleation. The in situ-generated acetate anions further enhance ZnBD production by promoting the deprotonation of the organic ligands. Additionally, these acetate anions serve as coordination modulators, enabling the production of one-dimensional nanorod crystals with controlled sizes and aspect ratios. As a proof of concept, ZnBD is transformed into N/O-co-doped nanoporous carbon through pyrolysis in an Ar atmosphere, demonstrating its potential as an anode material for potassium-ion batteries. The results of this study advance the facile large-scale production of ZnBD and expand the application potential of ZnBD-derived materials.
Keywords: Ambient conditions; Derived carbons; Ion batteries; Metal acetate; Metal-organic framework-derived carbon; Metalorganic frameworks (MOFs); Pillar-layered metal-organic framework; Potassium ion battery; Potassium ions; Scalable synthesis; Ambient condition; Metal acetate; MOF-derived carbons; Pillar-layered MOF; Potassium ion batteries; Scalable synthesis